Eco-Enzyme-Based Dishwashing Soap Production as a Step Toward Achieving a Green Pesantren - Rahmayani, Ratu Fazlia Inda; Sulastri, Sulastri; Ramli, Ichwana; Warlaini, Ana (Universitas Syiah Kuala, 2025)
The Integrated Islamic Boarding School Al Falah Abu Lam U produces approximately 30 kg of organic waste daily, primarily from dormitory activities. This waste has not yet been optimally managed by the pesantren. Given its composition, the waste has significant potential to be converted into eco-enzyme (EE), which can be utilized as fertilizer and dishwashing soap for the pesantren's needs.This community service initiative applies science and technology, particularly in the field of biotechnology transformation during the fermentation of fruit peels into EE, and organic chemical transformation in the process of converting EE into dishwashing soap. The program has successfully trained male and female students (santriwan and santriwati) as well as female teachers (ustadzah) in sorting organic waste and processing it into EE. Approximately 100 kg of fruit peels have been fermented into EE, and participants have also been trained in the production of dishwashing soap using the resulting EE.